Die Vegetation des Südtiroler Grödner Tales und ihre kartographische Darstellung - Meurer, Manfred (ERDKUNDE, 1982)
Situated in the South Tyrolean Dolomites, the Grodner Valley runs in a west-east direction. Its plant cover, consisting of a great variety of species, is characterised by complex geological, morphological, edaphic and climatic conditions. It was possible to show that the distribution pattern of the vegetation is influenced not only by the niveau effect, which is caused by altitude, but also by the effect of relief as a result of exposition. Of additional significance is the sometimes considerable anthropogenic interference. With reference to the geofactors that characterize the region in this way the vegetation has been classified according to floristically and plant sociologically defined altitudinal levels. At the montane level the warmth-loving, sub-mediterranean, summer-green deciduous forests of the colline level, including their degradation stages, give way to extra-zonal firs and spruces on the shady side and azonal pines on the sunny one. At the sub-alpine level, on the other hand, there are extensive and hardier coniferous forests consisting of fir, larch and stone pine. Above the timber-line the spatially more restricted subalpine scrub societies are followed by lower alpine dwarf shrub societies and the upper alpine grass heaths. Only broken patches of pioneer turf and some rock plants advance even higher to the sub nival and nival levels.